Pregnant women's knowledge, attitude, and practice toward physical exercise during pregnancy and its associated factors at Dessie town health institutions, EthiopiaAJOG Global Reports at a Glance - Abdusellam Yimer, MSc; Seada Endris, MSc; Alemtsehay Wossen, MSc; Mengistu Abate, MSc (Elsevier, 2024)
BACKGROUND: Physical exercise consists of planned, repetitive, and intentional movements that reduce the risk of pregnancy-related complications. Worldwide, there is a high rate of physical inactivity during pregnancy, including in Ethiopia, which has detrimental effects on both pregnant women and their developing fetus. OBJECTIVE: This study aimed to assess pregnant women's knowledge, attitude, and practice toward physical exercise during pregnancy and its associated factors among antenatal care attendants at health institutions in Dessie, South Wollo Zone, Amhara Region, Ethiopia, in 2023. STUDY DESIGN: An institutional-based cross-sectional study was conducted among 614 pregnant women receiving antenatal care between January 18, 2023, and February 25, 2023. The study participants were selected using systematic random sampling technique. Data were collected using a pretested, face-to-face interviewer-administered, and semistructured questionnaire. The data were cleaned, coded, and entered into EpiData (version 4.6; www.epidata.dk) and analyzed using SPSS (version 25; SPSS Inc, Chicago, IL). Bivariate and multivariate binary logistic regression analyses were performed to identify factors associated with knowledge, attitude, and practice toward physical exercise during pregnancy. Variables with a P value of <.2 in the bivariate analysis were transferred to the multivariate analysis. Finally, the adjusted odds ratio and 95% confidence interval with a P value of <.05 in the multivariate analysis were considered statistically significant. RESULTS: The study found that 56.3% of participants had good knowledge, 51.5% of participants had a favorable attitude, and 32.2% of participants practiced physical exercise during pregnancy. Age, educational level, and heard about physical exercise during pregnancy were positively associated with pregnant women's knowledge and attitude. In addition, age, antenatal care follow-up, no history of abortion, ever done physical exercise before becoming pregnant, and good knowledge were positively associated with pregnant women's practice of physical exercise during pregnancy. CONCLUSION: Our findings indicate that approximately half of the participants had good knowledge and a favorable attitude. However, almost one-third of the participants practiced physical exercise during their pregnancy. It is recommended that antenatal care providers advise pregnant women to strengthen their antenatal care follow-up and offer health education and counseling about the benefits of physical exercise during pregnancy.